2017
DOI: 10.1186/s40425-017-0301-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of patients with advanced sarcoma enrolled in early phase immunotherapy trials

Abstract: BackgroundImmunotherapies, specifically those based on immune checkpoint inhibitors, have shown promising activity in multiple tumor types. Other than mifamurtide (MEPACT®) for osteosarcoma approved by European Medicines Agency, there are no approved immunotherapies for sarcomas.MethodsWe analyzed medical records of patients with advanced sarcoma who were referred to Phase 1 clinic at MD Anderson and received an immunotherapy (checkpoint inhibitors, vaccines, or cytokine based therapies). Clinical parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 37 publications
2
109
0
Order By: Relevance
“…The dissociation in the expression of CD8 and and PD1/PD-L1 axis suggests that adenosarcoma is a less favorable target for PD1/PD-L1 checkpoint inhibitors [27] and may use an alternate immune escape mechanism. Further investigations are required to identify immunologic therapeutic targets that may affect uterine adenosarcoma or other soft tissue sarcomas [8,10,28].…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation in the expression of CD8 and and PD1/PD-L1 axis suggests that adenosarcoma is a less favorable target for PD1/PD-L1 checkpoint inhibitors [27] and may use an alternate immune escape mechanism. Further investigations are required to identify immunologic therapeutic targets that may affect uterine adenosarcoma or other soft tissue sarcomas [8,10,28].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, other investigators have demonstrated stable disease for 33% (3/9) in patients with metastatic or unresectable GIST treated with checkpoint inhibitor-based trials. 16 Interestingly, this tumor had a low density of CD3 + T cells, which is unique for this patient given that higher levels of CD3+ infiltrates may portend a superior PFS. 17 Furthermore, while the co-localization of CD163+ and PD-L1 was expected, the expression of FOXP3 largely in the absence of CD3+ and CD4+ was surprising.…”
Section: Discussionmentioning
confidence: 85%
“…21 Because imatinib has activity against IDO in the GIST microenvironment, 22 the combination of imatinib and anti-PD1 has been investigated in murine models with promising synergy, 14 but this has been less evident in a phase I clinical trial. 16 However, PD1 is probably critical because when KIT inhibition was combined with the CTLA-4 inhibitor ipilimumab, clinical outcomes did not appear improved. 23 PD-L1 expression in GIST can be heterogenous, particularly in higher-risk tumors, further strengthening the argument for combination immunotherapy, and a trial is now ongoing at UCLA (NCT02880020) comparing single-agent nivolumab (anti-PD-1) alone or in combination with ipilimumab (anti-CTLA-4).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating epidemiological data showed that the treatment for OS has remained essentially unchanged since the 1970s. e survival rates of OS patients were likewise maintained [53,54]. A more intensive understanding of the mechanisms that drive metastasis and tumor heterogeneity coupled with available and clinically annotated data sets is urgently needed in the clinic.…”
Section: Discussionmentioning
confidence: 99%